Criminal procedure in Syariah Court - Ab Aziz, Shamrahayu (Sweet & Maxwell Asia, 2011)
Criminal procedure is the branch of law containing the rules governing the administration of criminal justice. It commences with investigation and ends with discharge or acquittal, or with conviction and imposition of sentence and punishment against the accused/convicted persons. The law aims to ensure a proper, fair and just process in the enforcement of criminal law. Islamic law has the same concept with specific rules governing the administration of criminal justice. Although Islamic criminal procedure contains sufficient basis and conceptual ideas supported by the primary and secondary sources of Islamic law, it is historically less developed compared to other branches of law.